210k views
4 votes
-3a(a^2-10a+25)= expand it and it has to be in polynomial form

2 Answers

4 votes

Bro did you go in the next grade?

User MattW
by
4.5k points
7 votes

Answer:


- 3 {a}^(3) + 30 {a}^(2) - 75a

Explanation:


- 3a( {a}^(2) - 10a + 25)

Multiply each term in the parentheses by -3a


= - 3a * {a}^(2) - 3a * ( - 10a) - 3a * 25

Calculate the product


= - 3 {a}^(3) - 3a * ( - 10a) - 3a * 25

Multiplying two negatives equals a positive
( - ) * ( - ) \ = ( + )


= - 3 {a}^(3) + 3a * 10a - 3a * 25

Calculate the product


= - 3 {a}^(2) + 30 {a}^(2) - 75a

Hope this helps...

Best regards!!

User Crazypeter
by
5.1k points